2015
DOI: 10.1163/22134468-00002032
|View full text |Cite
|
Sign up to set email alerts
|

Attention Mediates the Effect of Context-Relevant Social

Abstract: Attention mediates the effect of context-relevant social meaning on prospective duration judgments Srinivasan, N.; Tewari, S.; Makwana, M.; Hopkins, Nicholas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In line with the social support hypothesis, Hopkins and Reicher describe a series of studies among Kalpwasis (i.e., participants at mass gatherings) in which the various difficulties that these individuals confront (e.g., illness, coldness) are perceived by high identifiers as collective challenges that invite and facilitate social support provision and social support acceptance. In line with the meaning hypothesis, shared identity as pilgrims is also shown to enhance the significance of the event so that the health challenges it presents are not simply endured, but actively enjoyed and cherished—precisely because they are experienced as identity‐affirming (see also Hopkins & Reicher, ; Srinivasan, Tewari, Makwana, & Hopkins, ).…”
Section: Social Identities As Psychological Resourcesmentioning
confidence: 82%
“…In line with the social support hypothesis, Hopkins and Reicher describe a series of studies among Kalpwasis (i.e., participants at mass gatherings) in which the various difficulties that these individuals confront (e.g., illness, coldness) are perceived by high identifiers as collective challenges that invite and facilitate social support provision and social support acceptance. In line with the meaning hypothesis, shared identity as pilgrims is also shown to enhance the significance of the event so that the health challenges it presents are not simply endured, but actively enjoyed and cherished—precisely because they are experienced as identity‐affirming (see also Hopkins & Reicher, ; Srinivasan, Tewari, Makwana, & Hopkins, ).…”
Section: Social Identities As Psychological Resourcesmentioning
confidence: 82%
“…In the former case, pilgrims found the clip more meaningful and interesting, less uncomfortable, and they also chose to listen to it longer (Shankar et al, 2013). Moreover, the results of time perception studies conducted using this same clip showed that it was processed differently (attracting more attention) when it was designated Mela-related (Srinivasan, Tewari, Makwana, & Hopkins, 2015;Srinivasan et al, 2013). Again, the point is that what may appear to be intrusive 'noise' (and a stressor) can, when viewed from the vantage point of a particular identity, be meaningful 'sound' and contribute to positive affect which in turn means that well-being is maintained.…”
Section: C1 Affective Transformations: Health Benefitsmentioning
confidence: 97%
“…The noise of the crowd, at least when it derives from religious songs, chants and dramas, is experienced as a further affirmation of shared religious devotion and hence as non-intrusive (Shankar, Stephenson, Pandey, Tewari, Hopkins & Reicher, 2013). Indeed we even have evidence that noises attributed to the Mela, and hence seen as identity relevant, are encoded more richly and remembered better than identical noises attributed to non-identity relevant sources (Srinivasan, et al, 2013;Srinivasan, Tewari, Makwana, & Hopkins, 2015). Finally, as concerns the issue of proximity and the experience of disgust, we have evidence from elsewhere that bodily excreta (sweat in this case) are experienced as less disgusting when they emanate from an ingroup source (Reicher, Templeton, Neville, Ferrari & Drury, 2016) All in all, and across a series of modalities, we see that the identity relevance of stimuli -that is, precisely what they mean in relation to the self and whether they affirm or undermine the self, is critical to the way that they are encoded, evaluated and approached (or else avoided).…”
Section: Exploring the Dynamics Of The Variable Selfmentioning
confidence: 92%